The Relationship Between Contact Characteristics with TB symptoms Presence in Patientâs Contact of Pumonary TB BTA+ - Sari, Reny Mareta (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTTB patient can infect 10-15 people for 1 year, especially people with frequently direct contact with patients (WHO, 2014). The number of Pulmonary TB BTA+ patients in Puskesmas Tanah Kali Kedinding increase in 2011 to 2013. Every year, the number of population in the working area of the health center has the possibility of infected tuberculosis continues to increase. The objective of this research to analize the relationship between contact characteristic with TB symptoms presence in patientâs contact of Pumonary TB BTA+. This study used a cross sectional design. The samples were contacts of pulmonary TB BTA+ patients who were in Puskesmas Tanah Kali Kedinding Surabaya in 2013. Dependent variable is the status of the contact which is characterized by the presence of TB symptoms experienced after patient diagnosed pulmonary TB BTA +. The results of statistical tests with Î± = 0.05 showed that age (p = 0.010), contact-patient relationship status (p = 0.028), and residence (p = 0.027) had a relationship with the onset of symptoms the contacts of pulmonary TB BTA+. While the gender variable (p = 0.273), education level (p = 0.201), and employment status (p = 0.328) did not have a relationship with onset of symptoms on contact . It can be concluded that age, contact-patient relationship status, and residence had a relation with the onset of symptoms on contact while gender, education level, and employment status did not have a relationship onset of symptoms on contact of pulmonary TB BTA+.Keywords: contact, pulmonary TB, symptoms to contact